Design and fabrication of a dual band 1.8/2.5 GHZ antenna for RF energy harvester - Sampe, Jahariah; Yunus, Noor Hidayah Mohd; Yunas, Jumril; Pawi, Alipah; Rhazali, Zeti Akma (International Journal of Engineering and Technology, 2018)
This paper proposes a patch antenna that integrated with the RF energy harvester system. The research goal is to propose a slotted and shorted pin patch antenna, which offers a promising solution for efficient dual band RF receiver. A high gain and directivity parameter is desired to reach the goal as it defines the strength of an antenna in capturing more energy and to maximize the transferred power towards the harvesting system. The fabricated antenna on RT/Duroid 5880 is measured to evaluate the simulated results by CST-MWS. The measure-ment is carried in an anechoic chamber. The measured dual antenna gain is 2.29 dBi and 5.51 dBi at 1.8 GHz and 2.5 GHz band, respective-ly. The gain obtained by the proposed antenna is higher compared to the previous patch antenna designs in the frequency range of 1 to 3 GHz, with reasonable matching parameter. The antenna meets the acceptable specifications in the bandwidth range of 0.1 to 2.45 GHz, ex-hibit top omnidirectional pattern, the VSWR < 2 and the directivity > 7 dBi across the dual band. Thus, the proposed antenna is good enough to be adopted with the RF energy harvester.